2011
DOI: 10.2105/ajph.2011.300217
|View full text |Cite
|
Sign up to set email alerts
|

US Opinions on Health Determinants and Social Policy as Health Policy

Abstract: To examine what factors the public thinks are important determinants of health and whether social policy is viewed as health policy, we conducted a national telephone survey of 2791 US adults from November 2008 through February 2009. Respondents said that health behaviors and access to health care have very strong effects on health; they were less likely to report a very strong role for other social and economic factors. Respondents who recognized a stronger role for social determinants of health and who saw s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 33 publications
8
79
1
Order By: Relevance
“…Although the media's focus on behavioral causes and solutions may be productive, insofar as individual-level behaviors can produce near-term changes in health outcomes, recognizing the importance of social contextual factors is central to sustained and equitable improvements in the health of individuals and communities. Taken together, these media coverage patterns correspond to the aforementioned public opinion data (1, 2), suggesting that media coverage of disparities/SDH may be contributing to low public awareness and narrow perceptions of these issues—which, ultimately, could influence policy support for structural solutions to address disparities.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Although the media's focus on behavioral causes and solutions may be productive, insofar as individual-level behaviors can produce near-term changes in health outcomes, recognizing the importance of social contextual factors is central to sustained and equitable improvements in the health of individuals and communities. Taken together, these media coverage patterns correspond to the aforementioned public opinion data (1, 2), suggesting that media coverage of disparities/SDH may be contributing to low public awareness and narrow perceptions of these issues—which, ultimately, could influence policy support for structural solutions to address disparities.…”
Section: Introductionsupporting
confidence: 72%
“…However, local newspaper readership did not appear to translate into greater recognition of social contextual influences on health. Overall, SDH recognition was higher among City A residents than in national samples (2), but individual influences (e.g., personal health practices) were often rated as more important, regardless of newspaper readership (Supplementary Table S1). Thus local print news might have spurred awareness of disparities, but this coverage could have expanded that conversation to better underscore SDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work supports the notion that these indicators in Wisconsin are closely related to social determinants of health [28,[48][49][50][51]. The design of the current study did not accommodate controlling for social determinants of health.…”
Section: Implications Of Els Endpoint Response To City-bound Watershedssupporting
confidence: 53%
“…Despite the scientifically accepted construct of social determinants of health, a 2008–2009 national survey revealed that Americans believed health was most affected by individual behaviors and access to health care while social or economic factors were less important, and respondents who were non-White and lower income recognized a stronger role for social determinants (Robert & Booske, 2011). Respondents were also less aware of health disparities by race than by income (Booske, Robert, & Rohan, 2011).…”
Section: Rationale and Theoretical Underpinningsmentioning
confidence: 99%